2007
DOI: 10.1057/palgrave.thr.6050044
|View full text |Cite
|
Sign up to set email alerts
|

Families Travelling with a Disabled Member: Analysing the Potential of an Emerging Niche Market Segment

Abstract: The 2000 Census of Population indicated that 50 million Americans, or 19.3 per cent of the US population, were people with disabilities and covered under the Americans with Disabilities Act. It is estimated that the number of families with a member with a disability will grow significantly. Although people with disabilities and their families have sufficient discretionary income and time to take pleasure trips, tourism and hospitality marketers and practitioners to date generally have not much considered this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 51 publications
0
27
0
7
Order By: Relevance
“…This progress can be seen as an upward movement from the medical model, which views people with disabilities as patients, through the social model, which sees them as dependent individuals (Oliver, 1990), and into the economic model, which recognizes their consumer power as a lucrative market segment (Gröschl, 2007;Huh and Singh, 2007;Shaw, 2007;Shaw and Coles, 2004). Yet progress remains slow and myopic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This progress can be seen as an upward movement from the medical model, which views people with disabilities as patients, through the social model, which sees them as dependent individuals (Oliver, 1990), and into the economic model, which recognizes their consumer power as a lucrative market segment (Gröschl, 2007;Huh and Singh, 2007;Shaw, 2007;Shaw and Coles, 2004). Yet progress remains slow and myopic.…”
Section: Resultsmentioning
confidence: 99%
“…Il a pour mission la promotion et la valorisation de la recherche. www.erudit.org People with disabilities, together with family, friends and caregivers, constitute a large potential consumer market segment for the tourism and hospitality industry (Huh and Singh, 2007;Darcy and Dickson, 2009). Government authorities have reported that a considerable number of people have disabilities or are likely to acquire them over the coming decades (Cameron et al, 2010).…”
Section: Résumé De L'articlementioning
confidence: 99%
See 2 more Smart Citations
“…Bununla birlikte turizm alanyazınında engelli turistlere giderek dikkat çekildiği görülmektedir (Chou ve Chao 2007;Huh ve Singh 2007;Gröschl 2007;Yates 2007;Eichhorn vd. 2008).…”
Section: Nitel Araştırmanın Amacıunclassified